2005
DOI: 10.1007/s11262-005-1798-6
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Localization of Rice stripe virus Gene Products In Vivo

Abstract: The genome of the Tenuivirus, Rice stripe virus (RSV) comprises four RNAs, the smallest three of which each contain two open reading frames (ORFs) arranged in an ambisense manner. The expression of the ORFs from RNAs 2-4 in plants and the insect vector, Laodelphax striatellus, was studied using antisera raised against the gene products. In Western blotting of the proteins from infected plants, the molecular masses of p2, p3, pc3 (nucleocapsid protein, N) and p4 (major non-structural protein, NCP) were as expec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 34 publications
3
37
0
1
Order By: Relevance
“…The virus moves through the midgut, salivary gland, and ovary and is associated with amorphous or filamentous inclusions in the cytoplasm of midgut epithelial cells, salivary glands, and fat bodies (18,19). Using 454-FLX high-throughput pyrosequencing, Zhang et al (20) found that SBPH carries genes that play a role in regulating the innate immune systems, similar to those found in other insects, which may be involved in defense against viral infection.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…The virus moves through the midgut, salivary gland, and ovary and is associated with amorphous or filamentous inclusions in the cytoplasm of midgut epithelial cells, salivary glands, and fat bodies (18,19). Using 454-FLX high-throughput pyrosequencing, Zhang et al (20) found that SBPH carries genes that play a role in regulating the innate immune systems, similar to those found in other insects, which may be involved in defense against viral infection.…”
mentioning
confidence: 88%
“…The virus moves through the midgut, salivary gland, and ovary and is associated with amorphous or filamentous inclusions in the cytoplasm of midgut epithelial cells, salivary glands, and fat bodies (18,19). Using 454-FLX high-throughput pyrosequencing, Zhang et al.…”
mentioning
confidence: 99%
“…The cloned NS3 gene was composed of 636 nucleotides and 211 deduced amino acids. The nucleotide sequence generally shared a high degree of identity, ranging from 97 to 99%, with other NS3 genes already isolated from Korea (Lian et al, 2011), Japan and China (Jonson et al, 2009;Liang et al, 2005). The most similar nucleotide sequence already registered with GenBank, which differs in only two nucleotides, was Accession Y11095 from an isolate from Japan (Fig.…”
Section: Resultsmentioning
confidence: 73%
“…The open reading frame (ORF) consists of 636 nucleotides and 211 amino acids. The NS3 genes compared with YG-JN1 were selected from GenBank (NCBI) only with a high degree of similarity such as Y11095 (Liang et al, 2005), FJ602686 (Jonson et al, 2009), FN650803 (unpublished) and EF198724 (Xiong et al, 2009). Sanisbury and Lomonossoff, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, the timing of SP expression was earlier than CP (Wu et al, 2006). Furthermore, the expression of SP was limited to young leaf tissues early in the infection cycle (Liang et al, 2005). Thus, these results indicate that SP, a disease-specific protein which accumulates in infected plants, may be easily suppressed by antisense mediated RNA silencing.…”
Section: Rt-pcr Analysis Of Invading Viral Gene Expressionmentioning
confidence: 74%